Climatic fluctuations and the diffusion of agriculture - Quamrul Ashraf; Stelios Michalopoulos (Brown University, Department of Economics, 2013)
This research examines variations in the diffusion of agriculture across countries and archaeological sites. The theory suggests that a societys history of climatic shocks shaped the timing of its adoption of farming. Specifically, as long as climatic disturbances did not lead to a collapse of the underlying resource base, the rate at which foragers were climatically propelled to experiment with their habitats determined the accumulation of tacit knowledge complementary to farming. Thus, differences in climatic volatility across hunter-gatherer societies gave rise to the observed spatial variation in the timing of the adoption of agriculture. Consistent with the proposed hypothesis, the empirical investigation demonstrates that, conditional on biogeographic endowments, climatic volatility has a non-monotonic effect on the timing of the adoption of agriculture. Farming diffused earlier across regions characterized by intermediate levels of climatic fluctuations, with those subjected to either too high or too low intertemporal variability transiting later.
Keywords: O11; O13; O33; O44; Q54; Q55; Q56; 330; Hunting and gathering; agriculture; Neolithic Revolution; climatic volatility; Broad Spectrum Revolution; technological progress; Agrargeschichte; Klima; Schock; Agrargesellschaft; Innovationsdiffusion; Theorie; Welt